Barn på handlingstidspunktet, voksen på domstidspunktet - Morten Holmboe (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Young offenders will normally be treated more leniently than adults. This is because their youth implies less culpability and makes punishment likely to be experienced as more severe. In two recent opinions, the Norwegian Supreme Court has held that the reasons for treating young offenders more leniently are weakened if a defendant has reached the age of 18 when judgment is passed. The author argues that this reasoning cannot be built on the UN Convention on the Rights of the Child, nor on Norwegian law as formerly interpreted by the Supreme Court. This is because doing so turns the mere passage of time since an offense into a de facto aggravating factor at sentencing. Likewise, the filing of an appeal against a judgment may lead to a harsher punishment simply because of the passage of time.